Footstep Power Generation using Piezo Electric Sensors - C. Ahalya; M. Vasavi; M. Prathyusha; S. Sania Afrin; S. Sravani (Journal of Power Electronics and Devices, 2022)
The country’s population is growing, and as a result, so is the demand for electricity. The amount of energy squandered is also rising in many different ways simultaneously. The primary approach is to regenerate this energy in a form that can be used. In this project, human footsteps are used to generate electricity, which is then used to recharge the battery. A battery that can be used to charge electronic gadgets stores the power. The Atmega 328 processor powers this system, which also includes an Arduino IDE, an RFID sensor, a USB cable, and an LCD. The system goes into registration mode when we turn it on. We are able to add three users. After each user has logged in, the system prompts them to swipe their cards and connect their chargers. Every user initially receives 5 minutes of charging time by default.